Repeated Winning and Losing Experiences in Chronic Social Conflicts Are Linked to RNA Editing Pattern Difference - Ru, Fu-Xia; Kong, Fanzhi; Ren, Chun-Yan; He, Yu-Shan; Xia, Shou-Yue; Li, Yu-Ning; Liang, Ya-Ping; Feng, Jun-Jie; Wei, Zhi-Yuan; Chen, Jian-Huan (Frontiers in Psychiatry, 2022)
Winner-loser effects influence subsequent agonistic interactions between conspecifics. Although the role of A-to-I RNA editing has been recently implicated in chronic social defeat stress and aggressive behavior, it remains to be further elucidated in agonistic interactions, especially in the resulted repeated aggression (winners) and repeated defeats (losers). In the current study, transcriptome-wide A-to-I RNA editing in the dorsal striatum was investigated in a mouse model of agonistic interactions to generate aggressive winners and withdrawal losers. Our analysis identified 622 A-to-I RNA editing sites in the mouse striatum, with 23 to be differentially edited sites (DREs) in 22 genes, most of which were associated with neurological, psychiatric, or immune disorders. Among these DREs four missense variants were observed in neuroligin 2 (Nlgn2), Cdc42 guanine nucleotide exchange factor 9 (Arhgef9) BLCAP apoptosis inducing factor (Blcap), and cytoplasmic FMR1 interacting protein 2 (Cyfip2), as well as two noncoding RNA variants in small nucleolar RNA host gene 11 (Snhg11) and the maternally expressed 3 (Meg3) gene. Moreover, enrichment analysis indicated significant changes of functions and pathways in genes with A-to-I RNA editing, especially in winners. Our results demonstrate that winner-loser effects are linked to A-to-I RNA editing pattern difference, underlining its role in the molecular mechanism of agonistic interactions between conspecifics.